Comparative transcriptome analysis suggests convergent evolution of desiccation tolerance in Selaginella species - Gerardo Alejo-Jacuinde; Sandra Isabel González-Morales; Araceli Oropeza-Aburto; June Simpson; Luis Herrera-Estrella (BMC Plant Biology, 2020)
Abstract Background Desiccation tolerant Selaginella species evolved to survive extreme environmental conditions. Studies to determine the mechanisms involved in the acquisition of desiccation tolerance (DT) have focused on only a few Selaginella species. Due to the large diversity in morphology and the wide range of responses to desiccation within the genus, the understanding of the molecular basis of DT in Selaginella species is still limited. Results Here we present a reference transcriptome for the desiccation tolerant species S. sellowii and the desiccation sensitive species S. denticulata. The analysis also included transcriptome data for the well-studied S. lepidophylla (desiccation tolerant), in order to identify DT mechanisms that are independent of morphological adaptations. We used a comparative approach to discriminate between DT responses and the common water loss response in Selaginella species. Predicted proteomes show strong homology, but most of the desiccation responsive genes differ between species. Despite such differences, functional analysis revealed that tolerant species with different morphologies employ similar mechanisms to survive desiccation. Significant functions involved in DT and shared by both tolerant species included induction of antioxidant systems, amino acid and secondary metabolism, whereas species-specific responses included cell wall modification and carbohydrate metabolism. Conclusions Reference transcriptomes generated in this work represent a valuable resource to study Selaginella biology and plant evolution in relation to DT. Our results provide evidence of convergent evolution of S. sellowii and S. lepidophylla due to the different gene sets that underwent selection to acquire DT